Variability And Rainfall Against Slope Failure For Penang Island - Kassim, Maimunah Abu (Universiti Sains Malaysia, 2017)
Rainfall is one of the factors that can cause slope instability problems in Malaysia especially Penang Island is one of the areas which have corrugated and hilly topography. Thus, this study had been done throughout the two locations in Penang Island and they are Air Itam and Batu Lanchang with the helps by one of the IDRISI Selva software. The objectives of this study are first to identify variability of climate change parameter, second to analyse using suitable model for landslide analysis and lastly to provide landslide susceptibility maps based on the rainfall distribution. This Yearly and monsoonal variations of long term rainfall (30 years) and (17 years) data were studied. From time series plot and for mean yearly variations, both Air Itam and Batu Lanchang provides positive trend. For mean monsoonal variations for Northeast monsoon and Southwest monsoon, both Air Itam and Batu Lanchang provide positive trends. The climate extreme indices analysis shows that climate change makes this region become wetter with high amount of rainfall in Northeast monsoon and Southwest monsoon. Overall, parameters used in landslide mapping of Air Itam and Batu Lanchang are elevation, land use, soil properties and rainfall intensity with the application of IDRISI Selva to identify risky areas that prone to landslide.